1982
DOI: 10.1017/s0007485300008634
|View full text |Cite
|
Sign up to set email alerts
|

The effects of natural enemies on the growth of Lantana in Brazil

Abstract: Observations were made over a two-year period on the growth and natural enemies of Lantana tiliaefolia and L. glutinosa growing naturally at nine sites covering different climatic areas of Parana State, south Brazil. Lantana was found to be subjected to continuous attack by insects and/or fungi throughout the year, with different species causing damage at different times. Temperate-climate sites had a more diverse complex of insects and a greater intensity of attack than warmer-climate sites. Shrubs in sites w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

1988
1988
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(38 citation statements)
references
References 10 publications
0
38
0
Order By: Relevance
“…In her review and evaluation of L. camara biocontrol programmes, Broughton (2000) found leaf-, flower-, and fruit-feeding insects to be the most successful biocontrol agents. But this author also suggested that new defoliating species should not be considered, because artificial defoliation experiments by Winder (1980) and Broughton (1999), showed that lantana was able to survive continual defoliation for at least 1 to 2 consecutive years. Winder and van Emden (1980) found that attack by insects reduces plant growth more than an equivalent amount of artificial clipping.…”
Section: Introductionmentioning
confidence: 99%
“…In her review and evaluation of L. camara biocontrol programmes, Broughton (2000) found leaf-, flower-, and fruit-feeding insects to be the most successful biocontrol agents. But this author also suggested that new defoliating species should not be considered, because artificial defoliation experiments by Winder (1980) and Broughton (1999), showed that lantana was able to survive continual defoliation for at least 1 to 2 consecutive years. Winder and van Emden (1980) found that attack by insects reduces plant growth more than an equivalent amount of artificial clipping.…”
Section: Introductionmentioning
confidence: 99%
“…Artificial defoliation experiments by Winder (1980) and Broughton (1999) demonstrated that when 100% of leaves were removed from a lantana plant every month over a 1-to 2-year period, the plant recovered. Insect feeding is more damaging than artificial removal of leaves (Broughton, 2000), but these experiments suggested that lantana is capable of compensating for insect defoliation (Winder, 1980;Winder and Van Emden, 1980;Broughton, 1999Broughton, , 2000.…”
Section: Discussionmentioning
confidence: 99%
“…Insect feeding is more damaging than artificial removal of leaves (Broughton, 2000), but these experiments suggested that lantana is capable of compensating for insect defoliation (Winder, 1980;Winder and Van Emden, 1980;Broughton, 1999Broughton, , 2000. None of the defoliating insects established on L. camara in South Africa, inflict damage throughout the year because of declining populations in autumn (Teleonemia scrupulosa Sta˚l) and winter (Uroplata girardi Pic and Octotoma scabripennis Gue`rin-Me`neville), creating a ''lag period'' in spring, when lantana plants recover from the previous season's damage (Harley et al, 1979;Cilliers, 1982Cilliers, , 1987Broughton, 1999).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inclusion of native and alien distribution data in model parameterization ensured that the complete range of environmental conditions in which lantana may occur was covered. Seasonal phenology data from the southern states of Brazil (Winder, 1980(Winder, , 1982 was used to fit growth parameters. Australia has extensive distribution data on lantana and this was reserved for model validation and thus not used in parameter fitting.…”
Section: Climex Parametersmentioning
confidence: 99%